Effect of Saluang Music on Systolic Blood Pressure And Fatigue in Patients with Chronic Kidney Disease Undergoing Hemodialysis - Lenni Sastra; Zulham Efendi; Cintya Angeline Prawesthi (Nursing Current: Jurnal Keperawatan, 2026)
Chronic kidney disease is a progressive and irreversible kidney disorder that, if it has reached an advanced stage, requires kidney replacement therapy, one of which is hemodialysis. Patients with hemodialysis experience several problems, including changes in blood pressure and fatigue. One therapy that can overcome changes in blood pressure and fatigue is traditional instrumental music therapy. This study aimed to determine the effect of traditional Indonesian instrumental music, saluang, on blood pressure and fatigue in chronic kidney disease patients undergoing hemodialysis. This type of research uses a pre-experimental design with a one-group pre-test-post-test research design. The number of samples was 20 people taken using a purposive sampling technique. Data analysis used the repeated ANOVA test. The results of the study showed that the average fatigue score before the intervention was 41.50, after the intervention was 37.45, and there was a difference between the fatigue score before and after the administration of traditional instrumental music: saluang, with a p-value = 0.000 (p-value <0.05). The average systolic blood pressure before the intervention was 177.50 mmHg, after the intervention was 172.55 mmHg, and there was a difference in the average systolic blood pressure before and after the provision of traditional instrumental music: saluang, with p-value = 0.001 (p-value <0.05). From this study, it can be concluded that there is an effect of instrumental music therapy on fatigue and blood pressure in patients undergoing hemodialysis. It is recommended for nursing services to make instrumental music therapy intervention one of the non-pharmacological therapies in reducing fatigue and blood pressure in patients undergoing hemodialysis.